Foreign Direct Investment in Regional Integration: Comparative Attractiveness in the CEMAC and UEMOA Economic Spaces - Ngongang, Elie (European Journal of Sustainable Development, 2012)
The competition or complementarity of foreign direct investment (FDI)attractiveness between economically similar regions located in the same continenthas not yet been up to now sufficiently explored in the literature. The purpose ofthis paper is consequently to contribute to this literature by determining whetheror not there exists a long-term relationship between FDI flows in the CEMAC andUEMOA regions of Central and West Africa. This hypothesis is tested in botheconomic spaces using a Vector Autoregression (VAR) model. The study showsthat the FDI flowing in the UEMOA zone directly attracts FDI flows in theCEMAC zone. These inflows improve the business environment in both regions.Overall, the study however finds that the long-term relationship which existsbetween these two regions is inclined to be more competitive rather thancomplementary.